Analyses of soil chemical properties on mineral soil and peat soil toward growth performance of pineapple (MD2) / Nur Syahidah Abdul Jalil - Abdul Jalil, Nur Syahidah (Faculty of Plantation and Agrotechnology, 2019)
There are confusing facts that the mineral soil is high in nutrient compared to the peat soil but most of pineapple in Malaysia were cultivated on the peat soil. Thus, a set of experiment was conducted to evaluate the relationship of chemical properties on mineral soil and peat soil toward growth performance of pineapple and to compare the early growth performance of MD2 pineapple that were cultivated on mineral soil and peat soil. The chemical properties such as soil pH, cation exchange capacity (CEC), soil salinity and nutrient contents which are phosphorus (P), potassium (K), calcium (Ca) and Magnesium (Mg) from both soil were analyzed. The growth performance (plant height, leaf length, leaf number and leaf width) of pineapple cultivated on different type of soil also were measured. Results showed peat soil significantly (p = 0.00) more acidic (3.49) compared to mineral soil (5.38). The pH of soil was influenced cation exchange capacity (CEC) of the soil which the CEC of mineral and peat soil was 18.85 cmolckg -1 and 2.82 cmolckg-1 respectively. Salinity of both soil indicate it was suitable for pineapple growth which between 1-2 dS/m. Mineral soil content high nutrient compared to peat soil especially for Ca (626.81 mg/L) and Mg (45.55 mg/L) content which contribute to high pH. While peat soil significantly high in P and K content compared to mineral soil. However, the growth performance of pineapple cultivated on both type of soil shows no significant difference (p≥0.05) except for leaf width. Furthermore, there were no relationship between chemical properties of soil toward growth performance of pineapple.